Theory and ideology in Indian sociology: Essays in honour of Professor Yogendra Singh - Singhi, Narendra K. (New Delhi Rawat Publications, 1996)
Despite immense potential for ideological and theoretical discourse regarding India$1 (Bs intellectual tradition, worldview, cultural pluralism and historical continuity, there is dearth of serious sociological work in this area. The erudite contribution of some Indian sociologists has provided a neat conceptual categorization, theoretical and philosophical discussion and a critique of Indian sociology. Yet, the vast and immense potential for cognitive reconstruction as a self-conscious reaction to overwhelmingly privileged colonial-imperial dominant knowledge, necessitates understanding and interpretation through not only contemporary empirical studies but also classical texts, regional literature and oral traditions.s